(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2018)
The study aims to generate a proposed training program based on the evaluated pedagogical content knowledge (PCK) and teaching efficacy belief (TEB) of secondary science teachers. In the research process, the developed questionnaires had been administered to 125 secondary science teachers of the second district of Quezon. Based from the obtained results from correlating the teachers’ PCK and science TEB in Biology, Chemistry, Physics and Earth Science, using the Pearson’s r in the four areas were 0.0116, 0.001, -0.036 and 0.087 respectively, and concluded that there is no significant correlation between the teachers’ PCK and science TEB, since the r values are less than 0.3, accordingly, the two variables have a weak correlation, which means that increases or decreases in PCK are not significantly correlated to the teachers’ TEB, which leads to a decision of accepting the null hypothesis. Furthermore, the PCK of the respondents were also thoroughly gauged which consisted the sub-categories subject matter knowledge, instructional objective and content, knowledge of students’ understanding and instructional representation and strategies. Based on the construed outcomes, a proposed training program was created. It was measured and has a weighted mean of 3.60 with a descriptive rating of highly acceptable. It means that the proposed professional development program can be utilized and feasible to produce a tangible result. Moreover, curriculum stakeholders may adopt the developed matrix to improve their teachers’ PCK also in other areas to enrich their knowledge of our nature of work especially in guiding students to understand and facilitate learning.